The role of user-generated content in the tourist area life cycle model: developing countries with negative destination images - WIJETHUNGA, W.M.H.U. (2023)
This thesis aims to examine how user-generated content (UGC) contributes to the destination image (DI) formation of developing countries with negative DI in the early stages of the tourism area life cycle (TALC). Tourism is one of the world’s top export categories and most developing countries heavily depend on their tourism income (Konstantakis et al., 2017). This dependency demands their attention on proper destination management and planning. Meantime, many developing countries are suffering from prolonged negative DIs, which affects their ability to achieve tourism success (Avraham and Ketter, 2016). TALC is a significant and useful destination management and planning model (McKercher and Wong, 2021). While there are many developing destinations in the early stages of the model, specifically exploration and involvement, these have not been adequately explored compared to its later stages. Further, the TALC literature calls for more research on understanding the impacts of different forces that bring change to destinations in order to manage tourism (Butler, 2011; Butler and Hart-Robertson, 2022). Despite the availability of such research on triggers of destination change (e.g., Berry, 2006; Kubickova and Martin, 2020), the influence of DI as a trigger bringing positive change to destinations in facilitating movement through its stages is not yet explored. Favourable DI is a core determinant of tourism success that influences tourists’ behaviour, including their engagement with word-of-mouth communication (Boo et al., 2009; McCartney 2008). With customer-to-customer communications becoming more trustworthy, UGC shared in social media as an organic information source has become more influential and trusted in tourism decision-making compared to marketer-controlled sources (Fotis et al., 2012; Gretzel and Yoo, 2008). Further, tourists have become DI co-creators with their UGC engagement (Mak, 2017). However, the potential role UGC plays in the early stages of TALC as a demand-side trigger or the UGC’s role in overcoming negative DIs of developing countries is undetermined in the literature. Against this background, the aim of this thesis was addressed by examining three research objectives: to examine the impact of negative DI on the early stages of the TALC; to explain the role of destination marketing organization (DMO) and UGC projections of DI on the DI of a destination in the early stages of the TALC; and, to conceptualise the influence of UGC in both the DMO’s DI projections in the early stages of the TALC and also mitigating negative DI. Bangladesh was identified as a suitable destination on which to base this research because it is in its early stages of TALC and has a prolonged negative DI. The research questions were approached from a relativist ontological position with a social constructionism epistemology. The context-specific meanings constructed by the DMO, and tourists were studied using a qualitative critical visual methodology. Visual data were collected from images shared on Instagram (UGC) and Bangladesh’s DMO online promotional platforms. Further, in-depth interviews were conducted with a DMO official and international tourists. The data were analysed using qualitative visual content analysis, cultural analytics, and thematic analysis. The findings of this thesis suggest that prolonged negative DI, the extent of congruity between both projected and perceived DI, and UGC are three forces affecting the transition of TALC in its early stages. UGC is found to act as a demand-side trigger that makes the destination more appealing to other travellers, fills the information gap that arises due to limited DI projections from the DMO and, hence, potentially contributes to attracting travellers to the destination during its early stages. Furthermore, UGC contributes to challenging and changing negative stereotypes and, thus, contributes to countering the prolonged negative DIs of a destination. In addition, results reveal interaction between the TALC and circle of representation (CoR), showing CoR is a valid model for understanding traveller behaviour in the early stages of TALC. Theoretically, this thesis contributes to the TALC and DI literature by conceptualising UGC as the key contributor in DI projections in the early stages of the TALC, which provides destination appeal for the potential traveller and potentially contributes to increasing traveller numbers to destinations in the early stages of the TALC. Further, this thesis improves the understanding of how the interrelating components of DI, i.e., cognitive, and affective DI, act in increasing the congruity between projected and perceived DI. Further, this thesis has practical implications for the DMOs, policymakers, and tourism supplies at destinations in the early stages of their TALC. DMOs are recommended to focus on overcoming the destination’s prolonged negative DI and perceived DI in their promotional objectives. They are further advised to improve their promotions by incorporating UGC into them and by capturing important insights by systematically analysing UGC shared online.